Implementation of Talent Management as a Strategy for Achieving Company Competitive Advantage - Hady Siti Hadijah (International Journal of Artificial Intelligence Research, 2022)
The challenges of the times and the talent shortage have compelled businesses to develop and implement effective human resource management methods. Talent management is one of the successful human resource management tactics applied. If a company or organization is able to recruit individuals who are superior to its competitors, it will be able to create a superior organization. The implementation of talent management will fail if it is not supported by a selection system, specifically a system for identifying attainable performance results. With the implementation of talent management, the objective of this study. This study employs a qualitative approach using the literature review method. In the era of globalization, the achievement of organizational goals in terms of productivity may always be accomplished with high-quality products that meet market demand. For this reason, the Company must be able to secure the availability of the required talent in a timely manner, in a number and diversity commensurate with current demands, and with qualities that can be realized within the constraints of the organization's competitive advantage. It may be claimed that the organization's survival is highly contingent on the effectiveness of this process in attaining its vision, mission, and strategic objectives.